2007
DOI: 10.1093/jac/dkm144
|View full text |Cite
|
Sign up to set email alerts
|

Community emergence of CTX-M type extended-spectrum β-lactamases among urinary Escherichia coli from women

Abstract: The study documented the community emergence of CTX-M as the predominant ESBL type among urinary isolates from women. The spread of CTX-M enzymes among isolates from young women is concerning and deserves close monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 8 publications
6
64
1
1
Order By: Relevance
“…Although our study showed a high prevalence of the international clone ST131 (20,32) among phylogroup B2 bla CTX-M-15 -and bla CTX-M-14 -positive isolates, the genetic diversity of the 43 UTI isolates examined supported previous reports showing diverse populations of E. coli carrying bla CTX-M genes (12,15,29). The further molecular typing of the resistance plasmids from these isolates showed that the dissemination of bla CTX-M-14 and bla CTX-M-15 was associated mainly with IncI1 and IncF repB plasmids of widely different sizes, which confirmed that different IncF plasmids are the most common mediators of CTX-M enzymes (12,16).…”
Section: Discussionsupporting
confidence: 88%
“…Although our study showed a high prevalence of the international clone ST131 (20,32) among phylogroup B2 bla CTX-M-15 -and bla CTX-M-14 -positive isolates, the genetic diversity of the 43 UTI isolates examined supported previous reports showing diverse populations of E. coli carrying bla CTX-M genes (12,15,29). The further molecular typing of the resistance plasmids from these isolates showed that the dissemination of bla CTX-M-14 and bla CTX-M-15 was associated mainly with IncI1 and IncF repB plasmids of widely different sizes, which confirmed that different IncF plasmids are the most common mediators of CTX-M enzymes (12,16).…”
Section: Discussionsupporting
confidence: 88%
“…A total of 37 unrelated PFGE patterns were identified among the bla CTX-M -containing E. coli isolates, and 1 closely related or indistinguishable PFGE pattern was found in 4 of the CTX-M-positive isolates (Table 2). This high clonal diversity observed among our bla CTX-M -containing E. coli isolates is coincident with similar results obtained in other studies (Velasco et al, 2007;Hernández et al, 2005, Ho et al, 2007Briñas et al, 2005), indicating that the wide dissemination of the bla CTX-M genes among E. coli isolates is mainly due to the horizontal dissemination of resistance determinants and not to dissemination of resistant clones. Nevertheless, the clonal dissemination of CTX-M-15-producing E. coli isolates within the hospital and community has been reported, and very recently, the intercontinental emergence of E. coli clone O25:H4-ST131 producing CTX-M-15 has been reported (Nicolas-Chanoine et al, 2008).…”
Section: Jmm Correspondencesupporting
confidence: 92%
“…Because all included patients were living in Phnom Penh, mediocre hygiene might have favored the diffusion of clones within an urban area, a phenomenon that had previously been observed in large-scale studies undertaken in the United Kingdom (12), Canada (36), Italy (37), and Brazil (15) but not in Hong Kong (13). In contrast to our results, clones identifi ed in those studies harbored the same β-lactamases.…”
Section: Discussioncontrasting
confidence: 81%